The Power of Far-Red Light at Night: Photomorphogenic, Physiological, and Yield Response in Pepper During Dynamic 24 Hour Lighting - Lanoue, Jason; Little, Celeste; Hao, Xiuming (Frontiers in Plant Science, 2022)
Supplemental light is needed during the winter months in high latitude regions to achieve the desired daily light integral (DLI, photoperiod x intensity) for greenhouse pepper (Capsicum annuum) production. Peppers tend to have short internodes causing fruit stacking and higher labour time for plant maintenance when grown under supplemental light. Far-red light can increase internode length, and our previous study on tomatoes (Solanum lycopersicum) also discovered monochromatic blue light at night during continuous lighting (CL, 24h) increased stem elongation. Furthermore, the use of a low intensity, long photoperiod lighting can reduce light fixture cost and overall electricity costs due to lower power price during the night. Therefore, we investigated the use of blue and/or far-red light during the night period of CL to increase stem elongation. Three pepper cultivars with different internode lengths/growing characteristics (‘Maureno’, ‘Gina’, and ‘Eurix’ ) were used to investigate the effects on plant morphology in a short experiment and one cultivar ‘Maureno’ was used in a long experiment to assess the impact on fruit yield. The five lighting treatments that were used are as follows: 16h of white light during the day followed by either 8h of darkness (16W - control), white light (24W), blue light only (16W+8B), blue + far-red light (16W+8BFR), or far-red light only (16W+8FR). Calculated nighttime phytochrome photostationary state (PSS) was 0.833, 0.566, 0.315, and 0.186 for 24W, 16W+8B, 16W+8BFR, and 16W+8FR respectively. All five treatments had the same DLI in photosynthetically active radiation (PAR) and far-red light. The 16W+8BFR and 16W+8FR treatments significantly increased internode length compared to 16W and 24W but neither was more impactful than the other. The 16W+8B treatment also increased internode length but to a lesser extent than 16W+8BFR and 16W+8FR. This indicates that a nighttime PSS of 0.315 is sufficient to maximize stem elongation. Both 16W+8B and 16W+8BFR drove photosynthesis during the nighttime supporting similar yield compared to 16W. Therefore, 16W+8BFR is the most potential lighting strategy as it can lead to a greater reduction in light fixture and electrical costs while maintaining yield and enhancing internode length.